2016
DOI: 10.14710/jpk.4.1.29-39
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Berhubungan Dengan Pemanfaatan Pelayanan Kesehatan Di Wilayah Kerja Puskesmas Tambarana Kecamatan Poso Pesisir Utara Kabupaten Poso

Abstract: Abstrak. Puskesmas adalah fasilitas pelayanan kesehatan yang menyelenggarakan upaya kesehatan masyarakat dan upaya kesehatan perseorangan tingkat pertama, dengan lebih mengutamakan upaya promotif dan preventif, untuk mencapai derajat kesehatan masyarakat yang setinggi-tingginya di wilayah kerjanya. Pemanfaatan pelayanan Puskesmas dipengaruhi oleh beberapa faktor antara lain persepsi masyarakat tentang kesehatan, persepsi masyarakat tentang kualitas pelayanan, pendapatan keluarga dan tingkat pendidikan. Penelit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0
31

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 0 publications
5
22
0
31
Order By: Relevance
“…The using of health facilities could reflect the high incidence of ARI, that was 60% of outpatient visits in Puskesmas and 20-40% of outpatient visited in hospitals (IDAI, 2010). The results show that there is a relationship between the use of health services with the public's health perception (Napirah et al, 2016). Similar to this study, Wahyuni (2012) shows that there was a significant relationship between the utilisation of health services with the illness perception.…”
Section: Enabling Factors In Forming the Main Perceived Constructionsupporting
confidence: 84%
“…The using of health facilities could reflect the high incidence of ARI, that was 60% of outpatient visits in Puskesmas and 20-40% of outpatient visited in hospitals (IDAI, 2010). The results show that there is a relationship between the use of health services with the public's health perception (Napirah et al, 2016). Similar to this study, Wahyuni (2012) shows that there was a significant relationship between the utilisation of health services with the illness perception.…”
Section: Enabling Factors In Forming the Main Perceived Constructionsupporting
confidence: 84%
“…It indicated that the higher the income, the lower health care service utilization would be. This argument was supported by studies conducted by Napirah, Rahman and Tony (2016) and Putra (2010) which explained that there was a correlation between family income and health care service utilization, but the researchers did not elaborate more about the type of correlation. The access to health care services was sometimes hindered by inadequate financial and material resources which were characterized by poverty and material deprivation that built a barrier for the public to access health care services (Ursulica, 2016).…”
Section: The Correlation Between Income and Health Care Service Utilimentioning
confidence: 99%
“…Hence, the education variable might be related to health care service utilization by contribution beneficiary patients. Based on research conducted by Napirah, Rahman and Tony (2016), it was proven that there was a correlation between family education and health care service utilization. A research conducted by Wardana (2017) also stated that there was a significant correlation between the education level of participants and health care service utilization in Rowosari Primary Healthcare Center.…”
Section: The Correlation Between Education and Health Care Service Utmentioning
confidence: 99%
“…Hasil ini sesuai dengan teori terdahulu yang mengemukakan bahwa penghasilan seseorang merupakan salah satu faktor yang dapat memengaruhi persepsi dikarenakan semakin tinggi penghasilan, seseorang akan memiliki tuntutan dan harapan yang lebih tinggi pada pelayanan kesehatan yang dibutuhkannya karena mampu secara finansial. Hasil ini juga sejalan pada penelitian (Vuong et al, 2017), seseorang dengan pemasukan atau penghasilan tinggi akan memiliki kebutuhannya dengan lebih baik dibandingkan pada seseorang dengan penghasilan rendah karena seseorang dengan penghasilan tinggi akan rela untuk membayar lebih untuk kebutuhannya dalam hal kesehatan dan mendapatkan pelayanan yg lebih baik (Napirah, 2016). Tingkat penghasilan yang rendah akan berkaitan erat dengan ketidakmampuannya dalam biaya transportasi ke pelayanan kesehatan atau biaya kebutuhan lain seperti kebutuhan sehari-hari sehingga tidak merasa butuh pelayanan kesehatan (Gaol, 2013), yang dalam konteks ini adalah layanan fisioterapi antenatal.…”
Section: Pendahuluanunclassified